PERFORMANCE OF LAYING BIRDS FED DIETARY LEVEL OF MONOSODIUM GLUTAMATE - Ibidiran, O. E.; Adu, O. A. (Nigerian Journal of Animal Production, 2024)
The study was carried out at the poultry unit of the Teaching and Research Farm, The Federal University of Technology, Akure. A total of 144, 16 weeks old Isa Brown were purchased They were fed commercial grower mash until they e reached 20% laying performance (22weeks of age) before they were subjected to the experimental diets for sixteen weeks. The pullets were weighed at the beginning of the study and randomly allotted to the experimental diets containing 0.00, 0.25, 0.50, 0.75, 1.00 and 1.25g/kg Monosodium Glutamate (MSG). Each treatment was replicated 4 times with 6 birds per replicate in a completely randomized design, data was analysed using SAS 2008. The birds were fed twice daily (morning and afternoon) and water was provided ad-libitum. The birds were housed in a three-tier cage system. Feed consumption and weight gain and live weight of birds at the last week of the experiment were recorded while feed conversion ratio (FCR) was calculated. Eggs were collected weekly and egg quality (egg weight, egg length, egg width, shell weight and shell thickness) were determined. The results showed that egg weight, egg length, egg width, shell weight and shell thickness were significantly influenced (p<0.05) by the treatments. Also, feeding birds with 0.75% MSG improved hen day production and feed efficiency through least feed conversion ratio. Egg weight, egg length and egg width of eggs gotten from birds fed 0.25% MSG diet were better.